A hierarchically three-dimensional CoNi/N-doped porous carbon nanosheets with high performance of electromagnetic wave absorption. (March 2022) - Wu, YuHan; Peng, Kangsen; Man, Zengming; Zang, Rui; Li, Pengxin; Liu, Shuaishuai; Wang, Siyu; Liu, Puyu; Li, Peng; Cui, Yihua
Abstract: Hierarchical microstructures perform increasingly vital roles in the design and preparation of high-performance microwave absorption materials because of their unique advantages. In this study, hierarchically three-dimensional CoNi/nitrogen doped porous carbon nanosheets (CoNi/N@PCN) was synthesized via an in-situ sodium chloride template strategy. The CoNi nanoparticles uniformly grow on the surface of the nitrogen doped carbon nanosheets. The obtained CoNi/N@PCN possesses hierarchical structures, including 0D CoNi nanoparticles, 2D N-doped carbon nanosheets, and 3D porous conductive carbon network. Moreover, the complex dielectric constant of CoNi/N@PCN is further adjusted to balance the impedance matching by nitrogen doping. The unique hierarchical architectures possess a large surface, various kinds of interfaces, abundant defects, and void spaces. Benefiting from these characteristics, the as-prepared CoNi/N@PCN demonstrates impressive microwave absorbing performance with the minimum reflection loss ( RL min ) value of −56.54 dB and an effective absorption bandwidth (EAB) of 4.65 GHz at 2.2 mm thickness. This strategy may open a way for the extensive synthesis of porous carbon magnetic absorbers for high-performance microwave absorption absorber. Graphical abstract: Image 1